Pengaruh Terapi Senam Kaki Dengan Kejadian Penurunan Kadar Glukosa Darah Pada Wanita Diabetes Mellitus II - Assyifa Irasuliyah Intang; Masriadi; Hasriwiani Habo Abbas (Window of Public Health Journal, 2026)
Type II diabetes mellitus is a metabolic disease characterized by impaired insulin secretion and insulin resistance, leading to elevated blood glucose levels. This study aims to analyze the effect of foot exercise therapy on reducing blood glucose levels in patients with type II diabetes mellitus at the Kassi Kassi Community Health Center in Makassar City. This study used a quasi-experimental design with a one-group pretest-posttest approach. The study sample consisted of 15 respondents selected through purposive sampling. Data collection was carried out by measuring blood glucose levels before (pretest) and after (posttest) the foot exercise intervention. Data were analyzed using statistical tests to determine the differences before and after the intervention. The results showed a significant decrease in blood glucose levels after the administration of foot exercise therapy, with a p-value of 0.001 (p<0.05). In conclusion, foot exercise therapy has a significant effect on reducing blood glucose levels in patients with type 2 diabetes mellitus. This intervention can be recommended as a non-pharmacological effort in the management of diabetes mellitus